Human dental pulp stem cell adhesion and detachment in polycaprolactone electrospun scaffolds under direct perfusion - Paim,A. (2018)
Cell adhesion in three-dimensional scaffolds plays a key role in tissue development. However, stem cell behavior in electrospun scaffolds under perfusion is not fully understood. Thus, an investigation was made on the effect of flow rate and shear stress, adhesion time, and seeding density under direct perfusion in polycaprolactone electrospun scaffolds on human dental pulp stem cell detachment. Polycaprolactone scaffolds were electrospun using a solvent mixture of chloroform and methanol. The viable cell number was determined at each tested condition. Cell morphology was analyzed by confocal microscopy after various incubation times for static cell adhesion with a high seeding density. Scanning electron microscopy images were obtained before and after perfusion for the highest flow rate tested. The wall pore shear stress was calculated for all tested flow rates (0.005–3 mL/min). An inversely proportional relationship between adhesion time with cell detachment under perfusion was observed. Lower flow rates and lower seeding densities reduced the drag of cells by shear stress. However, there was an operational limit for the lowest flow rate that can be used without compromising cell viability, indicating that a flow rate of 0.05 mL/min might be more suitable for the tested cell culture in electrospun scaffolds under direct perfusion.